An Illegal Dumping Detection System Based on Image Processing in OpenALPR - Nurul Kamilah Hussin; Fauzun Abdullah Asuhaimi; Nor Azlina Ab Aziz; Wan Zakiah Wan Ismail; Khairul Nabilah Zainul Ariffin; Shahnurriman Abdul Rahman; Syahida Suhaimi (Akademi Sains Malaysia, 2024)
Indexed by Scopus/MyCite